High performance aluminium composite brake rotor - Maleque, Md. Abdul; Abdulmumin, Adebisi Adetayo (2013)
In this invention, high performance multiple particle size silicon carbide reinforced aluminium composite brake rotor has been fabricated using a stir casting method in order to investigate the performance stability in terms of weight reduction, energy saving, lower temperature generation and less hot spot formation on the brake rotor surface. A mathematical model has also been developed to predict the influence of weight reduction on energy saving of composite brake rotor. Composite light weight brake rotor showed 50 % weight reduction, having the density of 2.82 - 2.9 g/cc and hence, 19 % energy savings compared to cast iron brake rotor. Minimum hot spot zone generation was obtained from the composite brake rotor due to lower surface temperature rise compared to cast iron. The actual brake test and finite element simulation results on surface temperature rise showed a good agreement